Guidance note for CGIAR Genebanks on improving accession management - CGIAR Genebank Platform (2022)
The purpose of this note is to provide guidance for CGIAR Centers to harmonize aspects of their management of international collections of plant genetic resources for food and agricultural (PGRFA), including the vocabulary, form and scheduling of their joint communications concerning their management of those collections, within the context of existing applicable policies. The guidance note does not present a new policy per se; rather, it reflects and promotes best practices that Centers have developed over time in managing the international collections under the frameworks of, first, their 1994 In Trust Agreements with FAO and, later, their Article 15 Agreements with the Governing Body of the Plant Treaty.